Analisis Pengaruh Turunnya Tekanan Minyak Pelumas Terhadap Kinerja Motor Diesel Penggerak Utama - Abdurohman (LPPM AKMI SUAKA BAHARI CIREBON, 2022)
The AHTS Transko Balihe ship with a diesel motor as the main propulsion engine. Lubrication is a process that occurs in diesel motors with the aim of reducing the occurrence of heat due to friction, cooling the rubbing parts, avoiding the sound produced by the engine due to friction so that the engine sound will be smoother, avoiding power losses due to friction which means increasing mechanical immersion, and for surface protection against corrosion. The author in this study collected data on problems that arise, then literature studies and questionnaires or interviews which were then analyzed and presented descriptively. This discussion provides an overview of the causes of the decrease in lubricating pressure, namely in the sediment tank that lacks lubricating oil, dirty or clogged filters, too high or low viscosity of lubricating oil, less than optimal pump work, poor manometer, worn engine parts. And the decrease in lubricating oil pressure, such as hot temperatures, greater friction between pistons and cylinder liners and friction in the main bearings and crankpin bearings, also requires attention and maintenance of lubricating oil such as sediment tanks, clogged filters, viscosity of lubricating oil, pump relief work. the valve, the pipes that drain the lubricating oil, the condition of the manometer needle, some parts are worn